Implications of Educational Values in Surah Al-Kahf Verses 60-82 and Their Relevance to Education in Islamic Boarding Schools: A Case Study at Raudhatul Ulum Islamic Boarding School: Implikasi Nilai-nilai Pendidikan Pada Surat Al-Kahfi Ayat 60 - 82 dan Relevansinya Terhadap Pendidikan di Pondok Pesantren: Studi Kasus di Pondok Pesantren Raudhatul Ulum - Fitri Susanty (Pesantren Reviews, 2023)
The purpose of doing this research is to analyze the educational values in Surah al-Kahfi verses 60-82 and make a relationship or relevance to the educational process in Islamic boarding schools. In this study using qualitative research or library research. The reason is that the information used in this study is not in the form of numbers but in the form of data from both books and journals, all of which will be described clearly and in detail to develop an analysis of values education. In the qualitative research here, the researcher uses the library research method, which is a library research. The results of the study show that the educational values contained in surah al-Kaahf verses 60-82 are values that are include in the elements of education, namely educational goals, students, teachers, subject matter, educational methods and tools. In addition, there are also values of Islamic education in the story of Prophet Musa and Prophet Khidir in Surah al-Kahfi verses 60-82, these values include : high work ethic and never give up, patience, student;s ethic to the teacher, critical thinking, and faith value. And all the analysis obtained, if it is relevant to education in Islamic Boarding School, almost all values have applied and it is hoped that the result will be accordance with the content of surah al-Kahf verses 60-82